Sensitivity and Specificity of Several Malnutrition Screening Tools for Chronic Kidney Disease Patient: A Narrative Review - Qonita Rachmah; Dominikus Raditya Atmaka (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Malnutrition remains a critical risk factor for morbidity and mortality among CKD patients.However, malnutrition is preventable and treatable. Thus, early malnutrition screening of CKD patients iscrucial. The present paper is a narrative review of the several studies related the use, sensitivity and specificity ofdeveloped malnutrition screening tools for CKD patients.Material and Method: Articles were searched from five electronic databases i.e., PubMed, PMC, Semanticscholar, Science-direct, and Google scholar. Several keywords used for literature searching including“malnutrition screening tools CKD”; “malnutrition CKD”; “malnutrition screening CKD”. Inclusion criteriaof this narrative review was the subject of intervention should be an aged 1 – 64 years old with experimentalrandomized control trial (RCT) or non-RCT study design. The exclusion criteria for this literature studywere research published before 1990, literature studies, meta-analysis, comments, short communication, andeditorial letters. Data then narratively described.Result and Conclusion: Twelve publication were narratively described in final analysis. Development ofmalnutrition screening tools for CKD patient had been done since 1992 and still counting until 2020. At leastthirteen screening tools had been tested for its use, sensitivity and specificity. Among 13 tools we analyzed,Simple Nutrition Screening Tool (SNST) and The Renal Nutrition Screening Tool (R-NST) revealed thehighest sensitivity and specificity value which suitable to be used in adult population, while in children,only Pediatric Digital Scaled MAlnutrition Risk Screening Tool (PeDiSMART) showed a good sensitivityand specificity. Further study should be focusing to look for sensitivity and specificity in other specificpopulation to ensure the right use of malnutrition screening tool.